10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
BACKGROUND: The development of the International Consortium for Health Outcomes Measurement (ICHOM) standard sets reflects an increasing awareness of the need for systematic, standardised data collection on patient outcomes. OBJECTIVE: To describe the implementation of the ICHOM standardised set for hand and wrist conditions in the Department of Hand and Peripheral Nerve Surgery at a large, referral hospital in Sydney, Australia. METHOD: Patient outcomes were collected according to ICHOM-defined clinical pathways for three common procedures: carpal tunnel release, trigger digit release, and distal radius fixation. Response rates were recorded at preoperative and condition-specific follow-up time points over two 3-month periods before and after the employment of a dedicated research officer. RESULTS: Sixty-three patients were treated prior to the implementation of a research officer and 87 patients after. Pre-operative data completion improved from 35% to 93%; 3-month patient reported outcome measures from 25% to 64%; and 3-month clinician reported outcome measures from 0% to 40%. CONCLUSION: The ICHOM standard set was successfully implemented in an Australian public hospital, aided significantly by the employment of a research officer.Implications for health information management practice:Standardised outcome measurement can be embedded in existing clinical workflows utilising a framework including dedicated personnel, robust information technology infrastructure, and patient engagement strategies. This template is broadly applicable across institutions and facilitates a shift towards value-based healthcare metrics.